The Coriolis force and the concept of the Coriolis power plant - Janaszak, Tadeusz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
This paper presents analyses of the fictitious forces which are appearing where theframe of reference is moving simultaneously on the linear and rotational path. Finally, it givesa concept of the construction of a power plant. The power plant used the energy which derivedfrom the rotation of the Earth
Mathematical Economics; 2017; Nr 13 (20); s. 15-36
Keywords: complex number; derivative; Coriolis acceleration; Coriolis force; Coriolispower plant